The Women of Renaissance. Imogen and Nestan - Tamar Melikidze, (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2026)
The attitude of the Middle Ages and Renaissance regarding women gender is revealed in the present article. It is also discussed the literary image of the protagonist woman – Imogen in Shakespeare’s latest play Cymbeline . The fact that Imogen’s literary image shows some parallel lines with the main woman character of The Man in the Panther Skin is also revealed by the author.